The roots of plant defenses: integrative multivariate analyses uncover dynamic behaviors of gene and metabolic networks of roots elicited by leaf herbivory - Gulati, Jyotasana; Baldwin, Ian T.; Gaquerel, Emmanuel (The plant journal, 2014)
High-throughput analyses have frequently been used to characterize herbivory-induced reconfigurations in plant primary and secondary metabolism in above- and below-ground tissues, but the conclusions drawn from these analyses are often limited by the univariate methods used to analyze the data. Here we use our previously described multivariate time-series data analysis to evaluate leaf herbivory-elicited transcriptional and metabolic dynamics in the roots of Nicotiana attenuata. We observed large, but transient, systemic responses in the roots that contrasted with the pattern of co-linearity observed in the up- and downregulation of genes and metabolites across the entire time series in treated and systemic leaves. Using this newly developed approach for the analysis of whole-plant molecular responses in a time-course multivariate data set, we simultaneously analyzed stress responses in leaves and roots in response to the elicitation of a leaf. We found that transient systemic responses in roots resolved into two principal trends characterized by: (i) an inversion of root-specific semi-diurnal (12 h) transcript oscillations and (ii) transcriptional changes with major amplitude effects that translated into a distinct suite of root-specific secondary metabolites (e.g. alkaloids synthesized in the roots of N. attenuata). These findings underscore the importance of understanding tissue-specific stress responses in the correct day-night phase context and provide a holistic framework for the important role played by roots in above-ground stress responses.